Decisions about deep brain stimulation therapy in Parkinson’s disease - Brandão, Pedro; Grippe, Talyta Cortez; Modesto, Luiz Cláudio; Ferreira, André Gustavo Fonseca; Silva, Flávia Martins da; Pereira, Flávio Faria; Lobo, Marcelo Evangelista; Allam, Nasser; Freitas, Tiago da Silva; Munhoz, Renato P. (Arquivos de Neuro-Psiquiatria, 2018)
Parkinson’s disease can be treated surgically in patients who present with motor complications such as fluctuations and dyskinesias, or medically-refractory disabling tremor. In this review, a group of specialists formulated suggestions for a preoperative evaluation protocol after reviewing the literature published up to October 2017. In this protocol, eligibility and ineligibility criteria for surgical treatment were suggested, as well as procedures that should be carried out before the multidisciplinary therapeutic decisions. The review emphasizes the need to establish “DBS teams”, with professionals dedicated specifically to this area. Finally, surgical target selection (subthalamic nucleus or globus pallidus internus) is discussed briefly, weighing the pros and cons of each target.
Keywords: Parkinson disease; deep brain stimulation; reference standards; basal ganglia; neurosurgical procedures